Infectious Postpartum Sacroiliitis: The Importance and Difficulty of Early Diagnosis - Vale-Fernandes, Emídio; Rodrigues, Fedra; Monteiro, Carla; Carvalho, Luís (Acta Médica Portuguesa, 2016)
The sacroiliitis accounts for about 1.5% - 10% of all cases of septic arthritis and it is strongly associated with gynaecological infections, pelvic trauma or drug abuse (3.4% - 12.8% of cases occur during the postpartum period). Early diagnosis is difficult because the symptoms are nonspecific in pregnancy and in the postpartum period, making the delay of treatment a serious risk of irreversible damage to the joint and development of post-infectious complications. The authors describe the case of a 37-year-old puerperal woman presented to hospital, weeks after urgent caesarean section, with endometritis, post-anesthetic epidural hematoma and secondary infectious postpartum sacroiliitis. The diagnosis of sacroiliac joints pathology during pregnancy and puerperium is challenging. The pathogenesis of infectious sacroiliitis results from local contamination by contiguous infection or hematogenous spread of bacterial infections. The prognosis is usually favorable and depends on early diagnosis and treatment.